COMMUNICATION INTERACTION IN CHILDREN WITH SPECIAL NEEDS DESCRIPTIVE STUDY - Suryanti, Poppy; Apriadi, Eko Aziz; LARAS, HENNY DEWI (Journal of Public Relations and Digital Communication (JPRDC), 2024)
This research explores communication interactions in children with special needs, with a focus on the challenges faced and the strategies used to overcome them. Through a descriptive approach, this research analyzes the communication patterns of children with autism spectrum disorders, speech disorders, and developmental delays. The research results show that environmental support, such as family involvement, the role of educators, and the use of augmentative and alternative communication (AAC) technology, is very influential in improving these children's communication skills. Personalized communication strategies based on children's specific needs have also proven effective in helping them overcome communication barriers. These findings emphasize the importance of a holistic and collaborative approach in supporting the communication development of children with special needs. With the right support, they have great potential to develop better communication skills, which in turn can improve their social participation and quality of life